The songs of Johanna Kinkel : genesis, reception, context - Bunzel, Anja (The Boydell Press, 2020)
Johanna Kinkel (1810-1858) was a German composer, music pedagogue, pianist, poet, writer, and activist. This is the first study to offer an exhaustive examination of Kinkel's published songs through the lens of her extraordinary biography and reception. Throughout her life, Kinkel was strongly invested in traditional family and household duties. First married to a Catholic book seller, she successfully filed for divorce in 1840, converted to the Protestant faith, and, in 1843, married the poet, professor, and revolutionary Gottfried Kinkel (1815-1882), with whom she had four children. Many of her love songs reveal a sense of emotional hardship and longing for support and recognition. Similar sentiments can also be traced in Kinkel's private letters. On the other hand, she challenged typical gender conventions of the time in these private correspondences, in her poetry, music, and writings, and through public socio-political participation. Her political songs to words by herself, by Gottfried Kinkel, and by some of their poet-friends draw on such themes as freedom and democracy and are anchored in the German democratic movement during the first half of the century. Furthermore, Kinkel treats in her songs such typical Romantic topoi as nature, loneliness, eternity, and night thoughts. Her compositional aesthetics range from simple strophic settings with straightforward harmony to more diverse harmonic progressions, rhythmic peculiarities, and complex musical interpretations of poetic Romantic irony. This book provides insights into the depth and width of Kinkel's song aesthetics and into her positioning within and between such domains as musical professionalism and amateurism and 'masculine' and 'feminine' musical styles. It argues that Kinkel's songs both reflect and transcend aesthetic, cultural, and socio-political facets typically associated with female composers of the first half of the nineteenth century, thus adding a new layer to our understanding of both the composer Johanna Kinkel and nineteenth-century song more generally.